Obesity and its relationship to chronic fatigue among kindergarten teachers (Journal of the College of Basic Education, 2022)
The current research aims to identify the level of obesity among kindergarten teachers and the level of chronic fatigue among teachers and the relationship of obesity to chronic fatigue according to the research sample. The researcher chose (100) kindergarten teachers from government kindergartens in a random way and after using the appropriate statistical means and obtaining honesty and consistency, the researcher found Obesity is somewhat prevalent among kindergarten teachers, and some teachers suffer from sad fatigue, and there is a correlation between obesity and chronic fatigue, and in light of the results, the researcher put forth some recommendations and suggestions key words (obesity - Chronic fatigue).